Technical audit of melt granulation knots in the production of mineral fertilizers using tower method - Склабинский, Всеволод Иванович; Скиданенко, Максим Сергеевич; Кононенко, Николай Петрович (Technology audit and production reserves, 2014)
The paper describes the results of the research, conducted on the experimental setup on studying the effect of frequency and amplitude of the forced signal, superimposed on the liquid jet, outflowing through the hole of the perforated granulator shell, and liquid level in the volume of the device, on the homogeneity of the resulting droplets. The study of this process is caused by the need to modernize the prilling (granulation) knots of mineral nitrogen fertilizers during their manufacture in towers in order to reduce production losses due to polydisperse fractional composition of the resulting granules. Experimental results show that the impact of various values of the impulse on the liquid jet leads to change of its disintegration mode and diameter of the obtained droplets. This points to the need to take into account the specified frequency action when using in calculations. Otherwise, polydisperse droplets are obtained. A combination of experimental results and theoretical studies was the basis for designing special-frequency generator, used in modernizing existing granulators in large scale production of mineral nitrogen fertilizers. The special-frequency generator allows to automatically detect and change the signal frequency when changing the level of the filled basket; improve the homogeneity of the resulting product by automatic determination of the acceptable frequency for obtaining monodisperse mode of the jet disintegration. The studies have allowed to develop equipment that made it possible to increase the monodispersity of the resulting product (more than 98% of the desired fraction), reduce the dust content from 0.8-1.2% to 0.05-0.2%, which has led to a decrease in losses during transportation and storage. In addition, dust emissions into the atmosphere have reduced from 200-250 mg/m3 to 25-40 mg/m3, and as a result, this has allowed to decrease specific energy consumption during production and improve the environmental situation in the production area.